Enterprise Architecture di Televisi Republik Indonesia (TVRI) Jawa Timur - Betrice Felita Florensia; Alexander Setiawan; Adi Wibowo (Jurnal Infra, 2015)
TVRI Jawa Timur is a company that works in broadcasting services. TVRI Jawa Timur provide programs for public such as information, education, entertainment or culture. The business processes of TVRI Jawa Timur are supported by information technology, but there is no integrated information system to manage data and information for all parts of the organization unit. Nowadays, TVRI Jawa Timur only use microsoft word, microsoft excel, application for video editing and applications from ministry of finance. Therefore it is necessary to analyze and design the enterprise architecture to support the company. The framework used to design enterprise architecture is Enterprise Architecture Planning. The first process is analyze the business model and company strategy. Next, analyze the business processes and the condition of information technology in the TVRI company. After that, the design of data architecture, application architecture and technology architecture are made for TVRI company.